Developing supplementary reading materials for grade 11 students at a multimedia study program - Nunun Nuki Erfiani; Ngadiso Ngadiso; Suparno Suparno (Studies in English Language and Education, 2019)
This research is aimed at developing a supplementary reading material to fulfill students' need in one of the multimedia study program at Mangelang, Indonesia, for learning reading. The design of this research is Research and Development. This research was oriented to the product development, and it was conducted in two main stages; (1) exploration stage and (2) product development stage. The exploration stage includes (1) literature review, (2) field study, and (3) need analysis. Meanwhile, the product development stage describes (1) the prototype development, (2) experts’ judgment, and (3) pilot. This research was conducted in a vocational secondary school involving an English teacher, two material experts, and students. The findings show that the existing textbook used to teach reading contains general English material and it is less specific to be used for the students at the program. Therefore, it implies that there should be supplementary reading materials for the teacher to develop reading to meet the needs of these students.